Dual-mode distillation essential oil extraction system with STFPID / Zuraida Muhammad ... [et al.] - Muhammad, Zuraida; Ismail, Nadiah; Mohd Yusoff, Zakiah; Rahiman, Mohd Hezri Fazalul (Universiti Teknologi MARA, Kedah, 2019)
This product offers the popular steam and hydro distillation in a single unit. The product design is tailored to suite domestic and household application. It comes in a counter- top easy-to-use unit, with a compact and presentable look. The efficiency is promising and it even conserves more energy as compared to its industrial counterparts. With selectable dual-mode distillation, the product covers broad spectrum of raw materials to be extracted. Top performance when this product designs including with self - tuning fuzzy PID controller(STFPID) to control temperature of induction heating system to provide the good quality of extraction. Targeted at low-income community or even cottage industries, this system is designed and developed with minimal cost in mind. The parts are easily replaceable with standard components available in the market. This effort might indirectly help us to preserve and promote Malaysian invaluable herbs globally